Mandy Gardner, A Space of One's Own (AmeriQuests)
This paper uses the framework of Virginia Woolf's Room of One's Own to discuss why there is a paucity of modern "homeless literature," meaning literature by people who have experienced homelessness about that experience. The paper concludes that lack of space - be it lack of housing but also lack of public space to accommodate people who are homeless - contributes to this lacuna.